Contemporary Collective Bargaining in Seven Countries - Cholette, Gaston (Relations industrielles / Industrial Relations, 1959)
The article reviews the book, "Contemporary Collective Bargaining in Seven Countries," by Ado[l]f Sturmthal et al., published by the Institute of International Industrial and Labor Relations, Cornell University.